The autonomy of sport concept: a scoping review - Smirnova, Viktoriia; Jaén, Pedro José Mercado; Preuss, Holger; Könecke, Thomas; Schubert, Mathias (Frontiers in Sports and Active Living, 2025)
The autonomy of sport concept can be considered a fundamental principle within international sport governance. In essence, the principle signifies the right to self-regulation and reflects the ability of sport governing bodies (SGBs) to determine their own structures and rules, free from interference by external actors. Despite growing academic and practitioner interest, there is still no consensus as to what the term “autonomy” exactly means and how widely the principle is (supposed to be) applied in a changing world of sport. This article systematically maps the extent of research on the concept of sport autonomy, including its applications and limitations. Based on the PRISMA Extension for Scoping Reviews (PRISMA-ScR), our review identified 205 records examining sport autonomy between 1982 and 2024. The results reveal a notable increase in sport autonomy research over the last decade, demonstrating the increasing importance of the topic. The majority of records is non-empirical and focus on international multi-sport governing bodies, highlighting a Western-dominated nature on sport autonomy. Based on a qualitative content analysis, we contribute to theory by extending the multidimensional understanding of sport autonomy. Autonomy is a dynamic and multifaceted concept that needs to be studied in the dimensions of the interlinked autonomies. Our findings indicate that the borders between autonomies in sport governance practice are ambiguous, calling for more empirically driven research in future assessments. The great heterogeneity of SGBs requires a sophisticated deconstruction of different dimensions and conceptualisations of autonomy of sport, focusing on autonomy as a spectrum.